Female criminals in India : a psychological study of inmates of Nari Bandi Niketan - Ghosh, Shubhra (New Delhi : Uppal Pub. House, 1986)
Study based on data from the correctional center in Lucknow, Uttar Pradesh.
Includes index.
Bibliography: p. [195]-211.
mizan
Keywords: Nari Bandi Niketan (Uttar Pradesh, India); Female offenders -- India -- Uttar Pradesh -- Psychology